Lack of Implication among NGO Regulations in Pakistan: A Complicated Legislation System and its Impact on Asia and Europe - Ali, Mumtaz; David, Maya Khemlani (AEI Insights, 2021)
Pakistan is a fragile state with regard to lack of institutionalization, which can be seen ubiquitously. Pakistani national and provincial parliaments are engaged in formulating legislations. However, the violation and breaching of law is a common trend. NGOs mostly work for welfare, development, and advocacy. Evidence about regulation systems for citizen welfare show that several laws and legislations have been passed in parliament in relation to this welfare. However, implication is seriously lacking. Moreover, corruption and poor management in regulatory departments is a major challenge. Studies show that corruption exists both in NGOs and government departments. Currently, the work and importance of NGOs is increasing in Asia. Various regional, international and European organizations are supporting Pakistani NGOs. If effective measures are not taken by the Pakistani Government regarding effective NGO legislation and implementation, these supporting organizations may impose restrictions on their relief services to Pakistan. In his study, for the methodology, a literature review and In-Depth Interviews (IDIs) were employed.. NGO professionals, legal experts and regulatory body officials (Key Informants) were selected. The study found that NGO regulations are quite complicated in Pakistan. NGOs at times suffer from confused and complicated departmental conditions. Proper guiding protocols are not found in important departments. NGOs can be registered with six regulatory bodies in Pakistan. Furthermore, the government has also established a PCP to facilitate and monitor NGO activities. This paper analyzes the regulatory system, and discusses the pros and cons of the control mechanisms.